Experimental Studies Of Spray And Combustion Characteristics Of Biomass Derived Fuels In A Constant Volume Combustion Chamber - Soid, Shahril Nizam Mohamed (2013)
Concern with fossil fuel depletion and environmental degradation promotes the use of renewable energy sources in particular biomass derived fuel for automotive and power generation applications. In this study, spray characteristics of Refined Palm Oil (RPO) were studied in a Constant Volume Combustion Chamber (CVCC), and compared to conventional fuel such as gasoline and diesel. For gaseous fuel, Producer Gas (PG) derived from biomass gasification were studied as its usage in IC engines degrades the engine performance at about 30-35 %. An optical CVCC with spray measurement setup was used to measure spray tip penetration, spray cone angle and spray area of liquid fuel (gasoline, diesel and palm oil blends). Injection starting pressure was varied by increasing or decreasing the thickness of adjusting shims of the injector. The starting injection pressures were studied at 20, 30 and 34 MPa. For Compressed Producer Gas (CPG) combustion and optimization study, it was tested at different Mass Increase Factor (MIF) of 0, 25 and 50 % of the air and fuel mixture. The optimization was conducted using Design of Experiments (DOE) method.